(untitled) (Journal of Medical & Health Sciences Review, 2025)
Introduction: Postpartum depression (PPD) is a serious public health concern in women that is prevalent worldwide. The PPD is associated with mood swings, fatigue, eating disorders, and, sometimes, may be associated with more serious impacts such as suicidal attempts. The information about PPD in the local population of Charsadda is not available; therefore, this study aims to investigate the prevalence and risk factors of PPD in the women of the district of Charsadda. Material and Method: The study sample consisted of women from District Charsadda, belonging to different age groups, who had delivered a child within the past six months. A detailed questionnaire was used for the collection of socio-demographic data, while for the PPD data, the Edinburgh Postnatal Depression Scale was used. A total score of 13 was considered positive. Results: The analysis indicated that 48 women out of the total 150 were depressed. The prevalence is 32% in this sample group. Furthermore, the age group 20-40, low economic status, multigravida status, and vaginal delivery were found to be significant risk factors for the PPD in these women. Conclusion: Information and awareness about the PPD in this population are required for the timely management of the condition to prevent adverse effects on mother and child. More detailed studies with a larger sample size are needed for a better picture of the diseases.